Greener Protocol for the Synthesis of Carbamates - Satheesh, A.; Usha , H.; Priya, D. S.; Hariharan, A. V. L. N. H.; Ramanjaneyulu, M. V. V. (Journal of Scientific Research, 2023)
An efficient and environmentally friendly protocol has been developed for synthesizing carbamates. Carbamate derivatives are frequently used as pesticides (insecticides, fungicides, and herbicides), as starting materials in producing paints and polyurethanes, and as protecting groups of amines in organic synthesis. It is a simple and solvent-free methodology to prepare primary carbamates in high yield and purity from compounds sodium cyanate, Phenol/alcohol, and TCA (Trichloro acetic acid). We reported the application of TCA as a mild, convenient and effective reagent for this transformation.